Pengukuran Level Kapabilitas (Capability Level) Tata Kelola Teknologi Informasi Pada Koperasi Unit Desa Mino Saroyo Cilacap Menggunakan Cobit 5 - Rizky Firdaus Kusuma Adjie; Resad Setyadi (JURIKOM (Jurnal Riset Komputer), 2022)
Information Technology (IT) investment in the Village Unit Cooperative (KUD) environment is influenced by the importance of information needed by rural communities. IT is very necessary to help performance to be maximized, especially in the KUD environment. In an effort to improve performance, KUD invests IT in several business fields. However, once the invested IT is not fully used according to its business goals. IT management is still the responsibility of each business field. Therefore, the results achieved are not comparable to what was expected after the implementation of IT. From these problems, it is necessary to have an IT Governance audit in order to find out the maturity value of the IT that has been implemented. This study aims to measure the it maturity applied by the Mino Saroyo Cilacap KUD, so it is necessary to use an international standard framework, namely control objectives for information and related technology (COBIT) version 5. The results of measuring the maturity level of IT Governance kud are currently estimated to be at level 2. The maturity level of the KUD at level 2 means that the KUD management process already has formal and written standard procedures. However, KUD has not carried out socialization to all levels of management and employees to be obeyed and carried out daily activities. The recommendations from this study provide problem solving as a reference to the KUD for improvement from the TKTI side so that it goes hand in hand with organizational goals and as expected by stakeholders in predicting the optimal use of IT resources.